The advancement of remote teaching, the growth of distance learning and the importance of the tutoring professional (Research, Society and Development, 2024)
Distance Learning is not new within pedagogical teaching processes. Since education began to be considered one of the main means of developing society, Distance Learning has created options to allow people to achieve the possibility of developing this space. The object of this article is the special training of teachers and even the professionalization of teachers as tutors. Analyzing and understanding Distance Education in Brazil is also observing how social and political movements have worked to allow education to be not only expanded, but also democratized. This research aims to describe the theory and analyze how it influences the process. Regarding the approach, it is defined as qualitative research, which critically analyzes the information collected and the data to be developed. This article discusses the importance of the tutor in complementing learning, be it in any teaching model.